Vestibular rehabilitation with biofeedback in patients with central imbalance - Bittar,Roseli Saraiva Moreira (2011)
Central Nervous System disorders may cause important functional unbalance in the maintenance of balance and posture. There is no effective rehabilitation for these symptoms until now. OBJECTIVE: The aim of this paper is to evaluate the use of tongue electrotactile stimulation on patients with central imbalance using BrainPort. MATERIALS AND METHODS: This is a prospective case series study. We evaluated 8 patients with central imbalance, 6 men and 2 women, with mean age of 67.75 years. The patients were submitted to Computed Dynamic Posturography (CDP) and then received 18 sessions of electrotactile stimulation by BrainPort® device for 20 minutes, twice a day. Then they were submitted to a new CDP test and to a self-perception scale to assess symptom remission, partial improvement and no improvement at all. RESULTS: 75% of the patients reported being more stable. There was no improvement in the balance control of the mass center in these patients. CONCLUSION: The patients were able to use the electrotactile stimulus to improve their balance control.